Clean Code - Martin, Robert (Addison-Wesley Professional, 2016)
Expanded Edition (August 2018) Updated with Design Patterns episodes from the Clean Code series from Clean Coders by "Uncle Bob" Martin. The Clean Code Video Series contains selected episodes from Uncle Bob's Clean Code series at CleanCoders.com, including: Fundamentals Advanced TDD Design Patterns Behavior Driven Development Clean Coder Overview Get ready for something very different. This ain't no screen cast. This ain't no talkin' head lecture. This is an Uncle Bob Video! This is like watching Uncle Bob on stage, but more so. This is high content education that will hold your attention and stimulate your thoughts with its impactful and energetic style. Related Content: Clean Code [Book] The Clean Coder [Book] Clean Architecture [Book] Clean Code Applied [Video] About Robert "Uncle Bob" Martin Robert Martin (Uncle Bob) (unclebobmartin) has been a programmer since 1970. He is the Master Craftsman at 8th Light inc, co-founder of the on-line video training company: cleancoders.com, and founder of Uncle Bob Consulting LLC. He is an acclaimed speaker at conferences worldwide, and the author of many books including: The Clean Coder, Clean Code, Agile Software Development: Principles, Patterns, and Practices, and UML for Java Programmers. He is a prolific writer and has published hundreds of articles, papers, and blogs. He served as the Editor-in-chief of the C++ Report, and as the first chairman of the Agile Alliance. He is the creator of the acclaimed educational video series at cleancoders.com . About Clean Coders Clean Coders is the leading producer of instructional videos for software professionals, taught in a way that both educates and entertains developers. Founded in 2010 by Robert "Uncle Bob" Martin and Micah Martin, Clean Coders has expanded to include a myriad of authors teaching an ever-increasing array of subject matters pertaining to clean code. Our training videos have inspired countless viewers to become the best developers they can be. cleancoders.com
Online resource; Title from title screen (viewed December 16, 2016)
Keywords: Electronic videos